Development of C-P and N-P bond formation reactions - Balázs, László Bertalan (Nanyang Technological University, 2020)
Chiral phosphine ligands are well-established as exceptional synthetic tools for various asymmetric transformations, since their discoveries at the beginning of the 1960’s. These important compounds can be synthesized via various catalytic and non-catalytic synthesis scenarios. Palladacycles are traditionally used as chiral resolving agents and chiral templates in asymmetric template promoted protocols for the generation of chiral phosphines. In recent years, palladacycles were found to be extraordinary catalysts in asymmetric hydrophosphination for C- and P-chiral phosphine syntheses. The P-H addition protocol to unsaturated double bond is a highly demanding strategy for C*-P bond formation, due to its atom economical nature and the variations of this reaction (C*-P* and O-P* bond formation protocols) can lead to the formation of numerous new chiral phosphine products. However, according to the investigations performed by our group, there are substrates which are significantly more challenging due to the relatively weaker double bond activation or chelating properties to the palladacycle catalyst. In this thesis, synthesis strategies are disclosed for novel C*-P, double C-P and N-P* bond formation for C- and P-stereogenic phosphine syntheses using P-H addition strategies. The generated chiral phosphines were applied in cyclometalation to obtain optically pure N-C(sp3)-E (E=S,O) type pincer complexes; coordination studies for chiral bimetallic palladium complex synthesis; and derivatization resulted in the formation of enantioenriched P-chiral diarylphosphinates. Mechanistic studies supported by NMR investigations revealed important aspects in the reaction mechanism of the new synthetic methods.